Barriers to mental health treatment in primary care practice in low- and middle-income countries in a post-covid era: A systematic review - Sahar Rameez; Almas Nasir (Journal of Family Medicine and Primary Care)
General primary care workers and family physicians are a crucial work force in managing the mental health of people in any given region. However, the barriers they face in low- and middle-income countries (LMICs) may be worsened by the pandemic. This review aims to bring together evidence about mental health treatment challenges experienced by people in LMICs in primary care settings. The review focuses on the shortage of essential mental healthcare services, stigma and lack of competent primary care professionals in establishing these services and their importance in the COVID-19 pandemic context. The systematic review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the search strategy included keyword search terms (MeSH) to perform a search across three electronic databases - Critical Appraisal Skills Program assessed PubMed, SpringerLink, and Cochrane and quality of the articles. The articles selected were analyzed through thematic analysis to identify the main themes and conclude our findings. Findings indicate that out of 1792 publications found, 14 studies matched the desired criteria for the studies. Endnotes, database search filters, and Covidence data extraction tools were used to generate the relevant articles in this study. This study shows that primary care institutions have financial and management issues in providing mental health services and a shortage of competent mental health experts in primary care, especially mental health–trained family physicians. The study also identifies community stigma as the most prevalent barrier to seeking mental health therapy, reflecting the lack of community health education in LMICs.